2010
DOI: 10.1111/j.1464-410x.2010.09662.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based determinants of radical prostatectomy surgical margin positivity

Abstract: Study Type – Prognosis (cohort)
Level of Evidence 2b What’s known on the subject? and What does the study add? Prior population and single‐centre studies have assessed incidence of positive surgical margins. The current study derived population‐based positive surgical margin cut‐offs in order to help identify underperforming surgeons who may benefit from further courses and/or self study to improve outcomes. OBJECTIVE • To characterize factors associated with positive surgical margins (PSMs) and derive popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
11
1
1
Order By: Relevance
“…The overall PSM rate in this study was higher than that of Western countries 12. A large proportion of our patients had PNI, a high Gleason score, a large number of positive cores in biopsy specimens, and/or high serum PSA, and may have been expected to have more advanced disease.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The overall PSM rate in this study was higher than that of Western countries 12. A large proportion of our patients had PNI, a high Gleason score, a large number of positive cores in biopsy specimens, and/or high serum PSA, and may have been expected to have more advanced disease.…”
Section: Discussioncontrasting
confidence: 54%
“…Owing to refinements in surgical technique and a downward stage migration during the PSA era, there was a decreasing tendency in PSM rate in Western countries recently. Williams et al 12. studied 4247 men diagnosed with prostate cancer who all underwent RP and found that PSM rate decreased from 21.3% in 2004 to 16.6% in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the study by Vesey et al [24], relying on data from the British Association of Urological Surgeons complex operations database between 2004 and 2009, the unadjusted rates of positive surgical margins and biochemical recurrence were significantly different above versus below a threshold of 15–20 cases per year. Nonetheless, these findings were not replicated in a population-based assessment examining the same end point [55]. Similarly, lymphadenectomy is important for staging and possibly improving oncologic control, although the latter remains controversial.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…25 To produce a meaningful predictive and quality control tool for urologists, our study had several advantages over the Williams study. First, our dataset contained the results of over 28 000 RPs which may have given it power to detect differences that were not statistically significant given their small sample size limited to the Medicare population.…”
mentioning
confidence: 99%